Lifetime impact of injury on education, employment and income for Australians of labour force participation age. (13th July 2016) - Callander, E. J.; Lloyd, C.
Abstract : Background: Research shows that employment rates are low post injury. Aims: To quantify the economic impact of a long-term injury and identify whether having a tertiary level of education attainment would offset this impact. Methods: Cross-sectional analysis of the 2012 Survey of Disability, Aging and Carers, which is nationally representative of the Australian population. Results: Males with any long-term injury had incomes 41% less than males with no chronic health condition (95% confidence interval [CI] −49.3%, −31.6%). For males with a long-term injury, there was no significant difference in the likelihood of being not in the labour force between those with and without a tertiary qualification (odds ratio [OR] 0.83, 95% CI 0.45–1.52). There was no significant difference in the incomes of females with any long-term injury compared with those with no chronic health conditions. For females with a long-term injury, there was a significant difference in the likelihood of being not in the labour force between those with and without a tertiary qualification (OR 0.37, 95% CI 0.17–0.80). If men with a long-term injury had the same probability of participating in the workforce as women, the percentage of men not in the labour force would reduce from 37 to 18%. Conclusions: Having a long-term injury was a significant personal cost in terms of labour force absence and lower income for males regardless of higher education attainment. For females, sustaining a long-term injury did not appear to significantly affect income.